We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
218
1
avatar+4684 

#9 Help.

 Feb 20, 2018

Best Answer 

 #1
avatar+7354 
+2

1)

P(x)   =   55,000√[x - 1945]

 

In which year was the population 275,000  ?

 

What is the value of  x  when  P(x)  =  275,000   ?

 

275,000   =   55,000√[x - 1945]

                                                     Divide both sides by  55,000 .

5   =   √[x - 1945]

                                             Square both sides of the equation.

25   =   x - 1945

                                             Add  1945  to both sides.

1970   =   x

 

In the year  1970  , the population was  275,000 .

 

2)

\(f(x)\,=\,\sqrt[3]{x-2}\)

                                       Instead of  f(x)  let's write  y .

\(y\,=\,\sqrt[3]{x-2}\)

                                       Now let's solve this equation for  x . Raise both sides to the power of  3

\(y^3\,=\,x-2\)

                                       Add  2  to both sides.

\(y^3+2\,=\,x \\~\\ x\,=\,y^3+2\)

                                       So the inverse function is...

\(f^{-1}(x)\,=\,x^3+2\)

.
 Feb 20, 2018
 #1
avatar+7354 
+2
Best Answer

1)

P(x)   =   55,000√[x - 1945]

 

In which year was the population 275,000  ?

 

What is the value of  x  when  P(x)  =  275,000   ?

 

275,000   =   55,000√[x - 1945]

                                                     Divide both sides by  55,000 .

5   =   √[x - 1945]

                                             Square both sides of the equation.

25   =   x - 1945

                                             Add  1945  to both sides.

1970   =   x

 

In the year  1970  , the population was  275,000 .

 

2)

\(f(x)\,=\,\sqrt[3]{x-2}\)

                                       Instead of  f(x)  let's write  y .

\(y\,=\,\sqrt[3]{x-2}\)

                                       Now let's solve this equation for  x . Raise both sides to the power of  3

\(y^3\,=\,x-2\)

                                       Add  2  to both sides.

\(y^3+2\,=\,x \\~\\ x\,=\,y^3+2\)

                                       So the inverse function is...

\(f^{-1}(x)\,=\,x^3+2\)

hectictar Feb 20, 2018

33 Online Users

avatar
avatar
avatar